Syn‐ and post‐eruptive gully formation near the Laacher See volcano. Issue 9 (4th May 2021) - Engel, Max; Dotterweich, Markus; Fülling, Alexander; Brill, Dominik; Broisch‐Höhner, Manuela; Totschnig, Ralf; Seren, Sirri; Kehl, Martin
Abstract: The Laacher See volcano (LSV) is located at the western margin of the Neuwied Basin, the central part of the Middle Rhine Basin of Germany. Its paroxysmal Plinian eruption c . 13 ka ago (Laacher See event; LSE) deposited a complex tephra sequence in the Neuwied Basin, whilst the distal ashes became one of the most important chronostratigraphic markers in Central Europe. However, some other impacts on landscape formation have thus far been largely neglected, such as buried gully structures in the proximity of the LSV. In this contribution, we map and discuss the spatial extent of these landforms at the site Lungenkärchen c . 4 km south of the LSV based on geophysical prospection as well as contrasting pedo‐sedimentary characteristics of the gully infill (particle‐size distribution, bulk‐sediment density, thin‐section analysis, saturated hydraulic conductivity) and the surrounding soils and tephra layers. These data are combined with a luminescence‐ and carbon‐14 ( 14 C)‐based age model that relates them to the LSE. It is demonstrated how these gullies seem to have been formed and rapidly infilled by rainfall and surface discharge both during and subsequent to the eruptive phase, with modern analog processes documented for the 1980 Mount St Helens eruption (Washington State, USA). Given the density of the gullies at the site and their deviating pedo‐sedimentary properties compared to the surrounding soils, we propose a significant influence on agricultural production in the proximity of the LSV, which remains to be tested in future studies. Finally, in contrast, gullies of similar lateral and vertical dimensions identified in post‐LSE reworked loess and tephra deposits of the Wingertsbergwand (close to the main study site and proximal to the LSV) have shown to be unrelated to the LSE and can either be attributed to periglacial processes at the Younger Dryas‐Preboreal transition or to linear incision during the early Holocene. Abstract : Linear subsurface gullies were identified close to the Laacher See volcano in magnetometer and ground‐penetrating radar prospection. Optically stimulated luminescence data indicate they incised during or shortly after the Laacher See event 13 ka ago. Pedo‐sedimentary characteristics of the gully infill differs from the surrounding regosols and brown earths, possibly influencing regional agricultural land use.